History of proliferative glomerulonephritis predicts end stage kidney disease in pure membranous lupus nephritis. (19th October 2021) - Fava, Andrea; Fenaroli, Paride; Rosenberg, Avi; Bagnasco, Serena; Li, Jessica; Monroy-Trujillo, Jose; Fine, Derek; Atta, Mohamed G; Petri, Michelle
Abstract: Objectives: Pure membranous (class V) LN is considered a less aggressive phenotype, but tissue fibrosis and chronic kidney disease may still develop. This study aimed to elucidate the prognostic value of a history of class switch in pure membranous LN. Methods: We included LN patients with at least two clinically indicated kidney biopsies. New onset of end stage kidney disease (ESKD) was defined as estimated glomerular filtration rate <15 ml/min/1.73 m 2, initiation of dialysis or kidney transplantation. Results: Among 220 patients (542 biopsies), 199 (90%) were female, and 118 (54%) were African American, 59 (27%) Caucasian, with median age of 28 years at the first kidney biopsy. Patients with pure class V in a first biopsy converted to proliferative LN in 41% of cases. Pure class V in a repeat biopsy was preceded by proliferative LN in 52%. Trajectory analysis of up to four repeat biopsies revealed that ISN class switch may happen at any time, even after multiple biopsies with the same class. New onset ESKD was observed within 2 years in 5/56 (9%) patients with pure class V in a repeat biopsy. All five patients had proliferative LN in the first biopsy (log rank P  = 0.024). Conclusions: The conversion from proliferative to membranous (and vice-versa) is frequent in SLE. It can occur at any time in the course of disease, limiting the prognostic value of the first biopsy. Evidence of prior proliferative LN is key as it is associated with higher risk of ESKD in non-proliferative LN.